Favourable 5-year postdischarge survival of comatose patients resuscitated from out-of-hospital cardiac arrest, managed with immediate coronary angiogram on admission. Issue 2 (1st June 2014) - Sideris, Georgios; Voicu, Sebastian; Yannopoulos, Demetris; Dillinger, Jean-Guillaume; Adjedj, Julien; Deye, Nicolas; Gueye, Papa; Manzo-Silberman, Stéphane; Malissin, Isabelle; Logeart, Damien; Magkoutis, Nikos; Capan, Dragos D; et al.
Abstract: Aims: On-admission coronary angiogram (CA) with angioplasty (percutaneous coronary intervention, PCI) may improve survival in patients resuscitated from out-of-hospital cardiac arrest (OHCA), but long-term survival data are scarce. We assessed long-term survival in OHCA patients managed with on-admission CA and PCI if indicated and compared survival rates in patients with/without acute coronary syndrome (ACS). Methods: Retrospective single-centre study including patients aged ≥18 years resuscitated from an OHCA without noncardiac cause, with sustained return of spontaneous circulation, undergoing on-admission CA with PCI if indicated. ACS was diagnosed angiographically. Survival was recorded at hospital discharge and at 5-year follow up. Survival probability was estimated by Kaplan–Meier survival curves. Results: A total of 300 comatose patients aged 56 years (IQR 48–67 years) were included, 36% with ST-segment elevation. All had on-admission CA; 31% had ACS. PCI was attempted in 91% of ACS patients and was successful in 93%. Hypothermia was performed in 84%. Survival to discharge was 32.3%. After discharge, 5-year survival was 81.7±5.4%. Survival from admission to 5 years was 26.2±2.8%. ACS patients had better survival to discharge (40.8%) compared with non-ACS patients (28.5%, p =0.047). After discharge, 5-year survival was 92.2±5.4% for patients with ACS and 73.4±8.6% without ACS (hazard ratio, HR, 2.7, 95% CI 0.8–8.9, p =0.1). Survival from admission to 5 years was 37.4±5.2% for ACS patients, 20.7±3.0%, for non-ACS patients (HR 1.5, 95% CI 1.12–2.0, p =0.0067). Conclusions: OHCA patients undergoing on-admission CA had a very favourable postdischarge survival. Patients with OHCA due to ACS had better survival to discharge at 5-year follow up than patients with OHCA due to other causes.